Synthesis of silver Nanoparticles@Carbon Dot nanocomposites using Aegle marmelos and Euphorbia hirta: Anti vibriocidal and antioxidant properties - Gali Raman; Sirangu Joseph; D Ramachandran; Phanindra Babu Kasi; Abhinash Marukurti; Alavala Matta Reddy; P Vijaya Nirmala; V S Manikanta; R. Lohitha Kavya; K Sarojani; Anitha Kadimi; Silpa Rani Medapalli; et al. (Results in Chemistry)
Vibrio parahaemolyticus (Vp) and Vibrio harveyi (Vh) are two pathogenic vibriosis causing agents which are prevalent in commercial aquaculture practices. In spite of the increasing Antimicrobial Resistance (AMR) in pathogenic organisms due to inappropriate usage of conventional antibiotics, there is an urgent need of alternative therapeutic antimicrobials. Metallic nanoparticles, particularly silver nanoparticles (AgNPs), are considered effective antimicrobials against a wide spectrum of microorganisms. Tunable properties such as size, shape, and surface functionalization enhance the properties and activities of AgNPs. Studies have explored the use of carbon dots (CDs) as an alternative source for reducing and capping AgNPs, given the limitations of using plant extracts as reducing agents for AgNP synthesis. Most of the studies synthesized CDs using various chemical precursors; however, plant-derived or biomass-derived CDs offer several advantages, such as biocompatibility, easy availability of precursors, renewability, hydrophilicity, and no requirement of heteroatom doping. In the present study, an eco-friendly hydrothermal technique was employed to synthesize high fluorescent, Biomass derived carbon dots (CDs) from the leaves of two medicinal plants, Aegle marmelos (AM) and Euphorbia hitra (EH). These CDs were then used as reducing agents for the green synthesis of silver nanoparticles (AgNPs). The absorbance peaks of synthesized AM CDs and EH CDs were at 267 nm and 274 nm, indicating π–π* electronic transitions. Upon adding CDs to AgNO3 led to a decline in CD absorption peaks and the emergence of AgNP SPR peaks at 467 nm and 479 nm, confirming AgNP formation. AM CDs showed a narrow peak at 530 nm (excitation at 360 nm), while EH CDs had a broad peak at 560 nm and AM CDs exhibited a narrow peak at 530 nm. AgNP@CD NCs did not emit luminescence, likely due to quenching during the AgNPs reduction. FTIR identified O-H, C≡C, and N-H functional groups in CDs. AgNP@AM CD NCs showed minor vibrational signals, while AgNP@EH CD NCs showed a complete reduction. The average particle sizes of the synthesized AgNPs were 8.51 nm and 23.59 nm for AM and EH, respectively. The synthesized AgNP@CD nanocomposites showed effective antivibriocidal activity with the lowest Minimum Inhibitory Concentration (MIC) of 3.9 μg/mL on Vibrio parahaemolyticus (Vp) by EH AgNP@CD NCs. The in vitro antioxidant studies revealed effective radical scavenging activity with the lowest IC50 value of 5.29 μg/mL on DPPH nitrogen free radical by AM AgNP@CD NCs. The present study found effective antivibriocidal and antioxidant properties of biomass derived AgNP@CD NCs.